Dynamics Analysis of Deployable Structures considering a Two-Dimensional Coupled Thermo-Structural Effect - Qi’an Peng; Sanmin Wang; Bo Li; Changjian Zhi; Jianfeng Li (International Journal of Aerospace Engineering)
The deployment accuracy of deployable structures is affected by temperature and flexibility. To obtain the higher accuracy, various measures such as the optimization design and the control process are employed, and they are all based on deployment dynamics characteristics of deployable structures. So a precise coupled thermo-structural deployment dynamics analysis is important and necessary. However, until now, only a one-dimensional thermal effect is considered in the literatures because of simplicity, which reduces the accuracy of the model. Therefore, in this paper, a new model coupling mechanical field with a temperature field is presented to analyze the deployment dynamics of a deployable structure with scissor-like elements (SLEs). The model is based on the absolute nodal coordinate formulation (ANCF) and is established via a new locking-free beam element whose formulation is extended to account for the two-dimensional thermally induced stresses due to the heat expansion for the first time. Namely, in the formulation, the thermal influences are along two-dimensional directions, the axial direction and the transverse direction, rather than along a one-dimensional direction. The validity and precision of the proposed model are verified using a flexible pendulum example. Finally, the dynamics of a linear deployable structure with three SLEs modeled by the element is simulated under a temperature effect.